Sexagem molecular em aves: contribuições à conservação biológica e á divulgação científica - Gonçalves, Bianca Picado [UNESP] (2013)
Birds represent a large part of the animals associated to illegal trade and commerce in Brazil, mainly due to some characteristics as song and feathers colors. Nowadays, genetic analyses comprehend one of the most efficient approaches to generate data in order to solve and minimize the results of environmental crimes and illegal trade of wild animals. Therefore, this work intent to perform sex identification genetic analyses in several birds, including species that are commonly associated to illegal animal trade and apprehended by the Environmental Policy and by IBAMA (Brazilian Institute of Environment and Renewable Natural Resources), and generate a scientific broadcasting material about illegal trade and conservation of this vertebrate group. DNA samples were obtained from feathers and blood of 124 individuals that belong to 53 species of the families Accipitridae, Cacatuidae, Cardinalidae, Cariamidae, Columbidae, Cuculidae, Emberezidae, Falconidae, Icteridae, Musophagidae, Psittacidae, Ramphastidae, Sturnidae, Thraupidae, Tinamidae, Trochilidae, and Turdidae, maintained by a Wildlife Reception, Screening and Rehabilitation Center (Floravida Institute NGO), a Wildlife Animal Health and Research Center (Faculty of Veterinary Medicine and Zootechny, São Paulo State University Botucatu, SP) and to two scientific breeding grounds of wild fauna based on conservation purposes (Criadouro C.A., Itatiba, SP and Criadouro Poços de Caldas, Poços de Caldas, MG). Sex-specific genetic profiles were generated by the amplification of DNA segments of the Z and W chromosomes. A primer set that anneal to exon regions of the CHD-Z and CHD-W (chromo helicase-DNA binding) genes and that amplify an intron region that differ in size between the two genes was used in PCR (Polymerase Chain Reaction) and the amplification products were visualized in 2% agarose gel. Two different size DNA fragments were evidenced for females and a single fragment was ...